2018
DOI: 10.1042/cs20180506
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of ceramides and their synthesizing enzymes for multiple sclerosis

Abstract: Ceramide synthases (CerS) synthesize chain length specific ceramides (Cer), which mediate cellular processes in a chain length-dependent manner. In experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), we observed that the genetic deletion of CerS2 suppresses EAE pathology by interaction with granulocyte-colony stimulating factor (G-CSF) signaling and CXC motif chemokine receptor 2 (CXCR2) expression, leading to impaired neutrophil migration. In the present study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…In addition, PICRUSt analysis revealed that the enriched KEGG pathways of gut microbiota in ITP mostly focused on lipid metabolism. Previous studies demonstrated important role of abnormal lipid metabolism in autoimmune diseases, such as diabetes and multiple sclerosis ( Kim, 2017 ; Kurz et al, 2018 ). Therefore, we proposed possible involvement of lipids and lipid-like molecules in the onset and development of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PICRUSt analysis revealed that the enriched KEGG pathways of gut microbiota in ITP mostly focused on lipid metabolism. Previous studies demonstrated important role of abnormal lipid metabolism in autoimmune diseases, such as diabetes and multiple sclerosis ( Kim, 2017 ; Kurz et al, 2018 ). Therefore, we proposed possible involvement of lipids and lipid-like molecules in the onset and development of ITP.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of ceramides have been observed in individuals with multiple sclerosis and in blood cells of experimental autoimmune encephalomyelitis mice, a model for multiple sclerosis (49). Through KO of CerS2 and CerS6 in experimental autoimmune encephalomyelitis mice, it has been proposed that the ratio of C16/C24-ceramide at the plasma membrane of neutrophils may regulate membrane properties and, thereby, the function of receptors and proteins important for cell migration.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Reportedly, ceramides and other sphingolipids possess important roles in various pathophysiological conditions, including stress responses, apoptosis, inflammation and proliferation [4][5][6][7][8] . Therefore, they are thought to be involved in the pathogenesis of various diseases, including diabetes mellitus [9][10][11] , neurodegenerative disorders 12 , multiple sclerosis 13 and coronary artery disease 14 .…”
Section: Introductionmentioning
confidence: 99%